Human Umbilical Cord Mesenchymal Stem Cell-Derived Exosomes Accelerate Diabetic Wound Healing via Ameliorating Oxidative Stress and Promoting Angiogenesis - Yan, Chenchen; Xv, Yan; Lin, Ze; Endo, Yori; Xue, Hang; Hu, Yiqiang; Hu, Liangcong; Chen, Lang; Cao, Faqi; Zhou, Wu; Zhang, Peng; Liu, Guohui (Frontiers in Bioengineering and Biotechnology, 2022)
Diabetic wounds remain a great challenge for clinicians due to the multiple bacterial infections and oxidative damage. Exosomes, as an appealing nano-drug delivery system, have been widely applied in the treatment of diabetic wounds. Endovascular cells are important component cells of vascular wall. Herein, we investigated the effects of HUCMSCs and HUC‑Exos on diabetic wound healing. In this study, HUVECs were co-incubated with HUCMSCs, and HUC‑Exos were utilized for in vitro and in vivo experiments to verify their roles in the regulation of diabetic wound healing. Our results demonstrated that HUCMSCs have an ability to regulate oxidative stress injuries of endothelial cells through exosomes and accelerate diabetic cutaneous wound healing in vitro. The present study suggests that HUC‑Exos accelerate diabetic cutaneous wound healing, providing a promising therapeutic strategy for chronic diabetic wound repair.